1993
DOI: 10.1136/bmj.306.6892.1584
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of cystic fibrosis testing in primary care: supply push or demand pull?

Abstract: Objective-To determine the acceptability and feasibility of screening for carriers of cystic fibrosis in a primary care setting.Design-Follow up study over 15 months of patients offered carrier testing by mouthwash.Setting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
115
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(126 citation statements)
references
References 20 publications
11
115
0
Order By: Relevance
“…Uptake was higher in family planning clinics "because a higher proportion of those attending were young and had not yet had children and, therefore, perceived the test as particularly relevant to them" and the authors also felt that those who attended the clinics to see their doctor because they were unwell were less likely to participate (Watson et al 1991b). Similar trends of lower uptake following an offer by letter, rather than directly by a clinician/researcher, were also seen in other UK (Bekker et al 1993;Payne et al 1997), USA Clayton et al 1996), and the Netherlands (Henneman et al 2001b;Henneman et al 2003;Lakeman et al 2009) studies. In Australia, the passive (i.e., without pre-test discussion) opportunistic offer of testing at GP and family planning clinics resulted in 43.5% uptake of testing.…”
Section: Preconception Carrier Screening For Cf In Primary Carementioning
confidence: 61%
See 1 more Smart Citation
“…Uptake was higher in family planning clinics "because a higher proportion of those attending were young and had not yet had children and, therefore, perceived the test as particularly relevant to them" and the authors also felt that those who attended the clinics to see their doctor because they were unwell were less likely to participate (Watson et al 1991b). Similar trends of lower uptake following an offer by letter, rather than directly by a clinician/researcher, were also seen in other UK (Bekker et al 1993;Payne et al 1997), USA Clayton et al 1996), and the Netherlands (Henneman et al 2001b;Henneman et al 2003;Lakeman et al 2009) studies. In Australia, the passive (i.e., without pre-test discussion) opportunistic offer of testing at GP and family planning clinics resulted in 43.5% uptake of testing.…”
Section: Preconception Carrier Screening For Cf In Primary Carementioning
confidence: 61%
“…In all of these studies, testing was offered free of charge to the research participants, and some also assessed knowledge and anxiety, typically finding that knowledge, while variable, was adequate though often decreased over time (Bekker et al 1993;Bekker et al 1994;Bernhardt et al 1996;Henneman et al 2002;Honnor et al 2000;Gordon et al 2003). Anxiety, while often higher in test-positive couples, also decreased over time (Bekker et al 1993;Bekker et al 1994). …”
Section: Preconception Carrier Screening For Cf In Primary Carementioning
confidence: 99%
“…There are some undeniable benefits in predictive genetic testing in diseases like MODY3 and HNPCC, and we should try to find the proper way to offer tests to different groups in society to ensure their awareness of these benefits, but simultaneously to remain non-directive. It has been shown for cystic fibrosis that a test offered directly from health professionals results in a higher uptake than if the test was merely known to be available [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…32 Evaluation of knowledge after receiving the test result has shown that carriers of CF had a higher level of knowledge as compared with noncarriers. 20,42,58,64 Knowledge decreased with the time elapsed since the test, 64 although this may be the case only for noncarriers, with no decrease in knowledge observed for carriers 3 months after testing. 58 The majority of those screened did not understand the concept of residual risk for future pregnancies, believing that a negative test result meant they had no chance of having a child with CF.…”
Section: Uptake Of Cf Carrier Screeningmentioning
confidence: 92%
“…33,34 When exploring the method of offering testing, 39-70% of the target population preferred to be offered testing in person rather than receiving the offer via a letter or brochure. 42,43 How information is provided has been explored, with 77-96% reporting brochures/information leaflets as useful. 14,21,41,44,45 The main information that potential participants wanted to receive was information about CF and screening, in particular, the risk of being a carrier and having a child with CF.…”
Section: How To Offer Cf Carrier Screeningmentioning
confidence: 99%